DI BALIK EKSOTISME: KEMISKINAN DAN KETIMPANGAN PROVINSI BALI DAN DAERAH ISTIMEWA YOGYAKARTA - Yusa, I Gede Putu Dharma (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.12.TAHUN.2024, 2025)
Numerous studies have examined poverty and inequality , yet comparisons between regions, particularly tourist destinations, remain limited . This study aims to compare the profiles of poverty and inequality between Bali and Special Region of Yogyakarta (DIY) Province over the past decade and to investigate the determinants of poverty in terms of education and employment. Data was sourced from publication by BPS-Statistics Indonesia and further analyzed using data from the National Socioeconomic Survey (Susenas) in 2014, 2019, and 2023. Poverty and inequality profiles were examined using the Foster-Greer-Thorbecke (FGT) index, the Gini ratio, Theil L index, and Growth Incidence Curve (GIC). Household-level determinants were analyzed through linear regression with Ordinary Least Squares (OLS), logistic regression, and Classification and Regression Tree (CART). The findings indicate that while both are tourist destinations, Bali has a better poverty and inequality profile than DIY. Over the past decade, Bali experienced pro-poor growth, whereas inequality in DIY increased due to non-pro-poor growth. Furthermore, this study finds that years of schooling and economic support ratio significantly enhance welfare or reduce the likelihood of poverty. Among the two determinants, the CART analysis shows that years of schooling are the primary determinant of poverty in these two provinces.